CORPORATE SOCIAL RESPONSIBILITY REPORTING IN LOCALLY OWNED HOTEL CHAINS IN SINGAPORE - Pang, Justin Matthew; Wee, Adrian Tiong Weng (Centre For Tourism Planning and Development, 2020)
This exploratory study looked at the Corporate Social Responsibility (CSR) programs of 10 locally owned and operated Singapore hotel chains. By using a Content Analysis methodology, the 10 hotel chains? CSR efforts were analysed vis-à-vis to their annual reports and websites. This gave clear indication of whether the hotel chains were complying with the promises and standards that they had stated and promised. This report found that the CSR reported by the hotel chains were inclined toward Environmental efforts. This could probably be due to this Environmental practice being more tangible and visible. It was also noted that while the initiatives taken by the hotel chains were relatively numerous, many failed to report on whether these efforts amounted to an achievement. Moreover, CSR reporting on the hotel chains? websites were almost non-existent. Given this, recommendations have been included to assist Singapore hotel companies manage their reporting of CSR activities.